2008
DOI: 10.2337/db08-0229
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Collateral Recruitment and Outward Remodeling in Experimental Diabetes

Abstract: OBJECTIVE-In this study, the effect of chronic hyperglycemia on acute ligation-induced collateral vasodilation, on monocyte chemotaxis, and on structural outward remodeling of collaterals was investigated.RESEARCH DESIGN AND METHODS-Femoral artery ligation was performed 8 weeks after alloxan or saline treatment in New Zealand White rabbits. Angiography was performed directly, 1 and 3 weeks after ligation. These angiographic recordings were used to quantify number of collaterals, lumen, and blood volume index. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 42 publications
0
32
0
3
Order By: Relevance
“…The monocyte migration toward CCL2 is also strongly reduced in diabetic rabbits with CLI, leading to a reduced blood volume index in the region of growing collaterals. 49 Baseline P-selectin level is 4-fold higher in T2D mice compared with wild-type mice but increases minimally at day 1 after CLI, whereas P-selectin content increases ≈10-fold in wild-type mice. Immunohistology of the hindlimb skeletal muscle demonstrates severely reduced monocyte recruitment in db/db mice compared with wild-type mice.…”
Section: Diabetes Mellitus and The Inflammatory Balance In Ischemic Mmentioning
confidence: 85%
“…The monocyte migration toward CCL2 is also strongly reduced in diabetic rabbits with CLI, leading to a reduced blood volume index in the region of growing collaterals. 49 Baseline P-selectin level is 4-fold higher in T2D mice compared with wild-type mice but increases minimally at day 1 after CLI, whereas P-selectin content increases ≈10-fold in wild-type mice. Immunohistology of the hindlimb skeletal muscle demonstrates severely reduced monocyte recruitment in db/db mice compared with wild-type mice.…”
Section: Diabetes Mellitus and The Inflammatory Balance In Ischemic Mmentioning
confidence: 85%
“…They explained the lower collateral development in hyperglycemic dogs by the fact that angiostatin showed an antiangiogenic effect. In another experimental study in rabbits with diabetes, it was shown that hyperglycemia had negative effects in all stages of collateral development [13]. There are conflicting reports about coronary collateral development in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, chronic diabetes mellitus is associated with enhanced angiogenesis in the eye (diabetic retinopathy) as well as in chronic wounds. On the other hand, chronic diabetes mellitus is associated with impaired collateral growth and arteriogenesis [15][16][17]. So far, there has been no good explanation for the angiogenic paradox in chronic diabetes mellitus.…”
Section: Vegf Resistance As the Previously Missing Link To Explain Thmentioning
confidence: 99%